Concise enantioselective synthesis of (+)-sertraline and (-)-CP-52002 using proline catalysis - Kalshetti, Rupali G.; Venkataramasubramanian, V.; Kamble, Sanjay P.; Sudalai, Arumugam (Tetrahedron Letters, 2016)
A short enantioselective synthesis of (+)-sertraline and its C-4 epimer (-)-CP-52002 with an overall yield of 30%, respectively, as its hydrochloride has been described. The key steps are the proline catalyzed Mannich reaction of acetaldehyde and acid catalyzed intramolecular Friedel-Crafts' alkylation reaction of olefin proceeding with high optical purities. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indatraline; Mannich reaction; Proline catalysis; Sertraline; Tametraline

Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.